Index, Volume 77 - 2006 : author / Indeks, Jaargang 77 - 2006 : outeur - Index Author (Journal of the South African Veterinary Association, 2006)
Index, Volume 77 - 2006 : author / Indeks, Jaargang 77 - 2006 : outeur